Comparison of GRM and GPCM in the Development of Higher Education Practice Assessment Instruments - Siti Maimunah; Zuhriyah Hidayati; Kusaeri Kusaeri; Suparto Suparto; Sita Isna Malyuna (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to outline various findings of previous research related to the comparison of the application of the Graded Response Model (GRM) and the Generalized Partial Credit Model (GPCM) in the development of higher education practice assessment instruments. This study uses the Systematic Literature Review. The data in this study are articles indexed in Q1, Q2, Q3, and Q4 from Scopus. Articles were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) technique. After going through the identification, screening, and eligibility process, 35 articles were included in the inclusion stage and analyzed using meta-synthesis techniques. The results of this study show that the findings of previous research show that the Graded Response Model (GRM) and the Generalized Partial Credit Model (GPCM) have differences in the development of practice assessment instruments in higher education. That GRM measures competencies based on students' values, attitudes, and spirituality, especially in assessments that use a graded scale such as Likert. In contrast, GPCM provides higher reliability in the context of step-based practice assessment or procedural stages. The results of this study can contribute positively to the development of practice assistance in higher education.